ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN METODE RISK BASED BANK RATING PADA PT BANK DANAMON INDONESIA, Tbk PERIODE 2014-2017 - Ardiani Hayumurti; R. Gunawan Setianegara (KEUNIS, 2019)
This research is conducted to identify the bank health rating of PT Bank Danamon Indonesia, Tbk one private bank in Indonesia in the period of 2014-2017 using the Risk Based Bank Rating (RBBR) method whether the bank is classified into one of the 5 categories: very healthy, healthy, healthy enough, not healthy enough, and unhealthy. Risk Based Bank Rating (RBBR) method is used to assess the health rating of bank based on 3 factors, i.e. Risk Profile, Earning, and Capital. This assessment with RBBR Method is done based on SEOJK Number14/SEOJK.03/2017 about the health assessment of conventional banks. The result of this research shows that: first, based on the credit risk aspect, the credit risk is low to moderate. Second, based on the liquidity risk aspect, the liquidity risk is healthy enough. Third, based on the remunerativeness seen by ROA and NIM ratio, the profitability is very adequate. Fourth, based on capital seen by KPMM or CAR ratio, the capital is very adequate